Viral hepatitis in children: state and prospects for solving the problem - L. G. Goriacheva; N. D. Ventslovayte; V. A. Greshnyakova (LLC "Diagnostics and Vaccines", 2021)
The problem of viral hepatitis (VH) today is an acute problem for the world healthcare system. Along with the COVID-19 pandemic, the VH pandemic claims up to 1.5 million lives annually. Since 2016, the Russian Federation has launched a WHO program aimed at combating VH. One of the first steps on the path of global elimination is getting rid of the virus in the small groups, among which micro-elimination in the child population is one of the promising areas.This review is devoted to the current state of the problem of VH in children in the Russian Federation today. The success of vaccine prevention (against viral hepatitis A and B) made it possible to achieve results in the form of a significant decrease in the incidence of children, minimizing the risk of perinatal infection. However, in recent years, there has been a progressive decline in vaccination coverage. This is mainly due to the growing popularity of anti-vaccination lobbies, a decrease in the awareness of patients and health workers about the need for timely vaccination, as well as the introduction of restrictive measures to prevent a new coronavirus infection. The emergence of mutant, "vaccine-eluting" strains, which are also resistant to available antiviral drugs, is another serious problem on the way to eliminating viral HBV. In the field of treating children with HBV, the possibilities are extremely limited, only 2 drugs are available, one of which (tenofovir alafenamide) is available only from the age of 12. Registration of direct antiviral drugs for the treatment of adolescents with chronic hepatitis C has made it possible to bring closer the goal of microelimination of the virus in children. However, the high cost of drugs poses a challenge for the state to introduce long-term benefit programs to ensure the availability of treatment. In addition, at the moment, the treatment of young children in our country remains a prospect for the future.Thus, despite significant advances in the strategy for the elimination of viral hepatitis, a number of problems remain relevant and present significant difficulties in achieving the global goal.